1030 An Exploration of the Impact of Cognitive Behavioural Therapy of Insomnia (CBT-I) on Perceived Cognitive Impairment in Breast Cancer Survivors. (27th May 2020) - Walsh, N; Garland, S; Lester, R; McCarthy, J; Laing, K
Abstract: Introduction: Insomnia and cognitive impairment are prevalent and persistent symptoms in cancer survivors. Cognitive Behavior Therapy is effective for improving insomnia and comorbid symptoms in cancer survivors but there are very few empirically supported treatments that can improve cognitive impairment. This feasibility study explored the impact of CBT-I on perceived cognitive impairment in breast cancer survivors. Methods: We enrolled 10 early stage breast cancer survivors with insomnia disorder and perceived cognitive impairment. Participants received 7 individual sessions of CBT-I over the course of 8 weeks and completed the Insomnia Severity Index (ISI), the Functional Assessment of Cancer Therapy - Cognitive Function (FACT-Cog) questionnaires and The Hospital Anxiety and Depression Scale (HADS) at baseline and post-treatment. Paired samples t-tests were used to assess change over time. Results: The sample was predominantly diagnosed with stage II breast cancer (60%). Women were an average age of 50.8 (SD 6.84) and 18.2 (SD 3.62) years of education. CBT-I significantly reduced insomnia severity [19.4 to 7.1; t(9)= 6.56, p < .001] and improved perceived cognitive impairment [t(9)= -3.55, p < .01], perceived cognitive ability [t(9)= -2.87, p < .05], quality of life [t(9)= -3.14, p < .05], and overall subjective cognitive function [t(9)= -3.67, p < .01]. Although participants began treatment with low levels of mood disturbance, CBT-I further decreased symptoms of anxiety (baseline: M= 10.10, SD= 4.34; post-treatment M= 8.20, SD= 3.91) and depression (baseline: M= 7.90, SD= 3.45; post-treatment M= 5.30, SD= 2.83), although not statistically significant. Conclusion: This study suggests CBT-I may improve perceived cognitive impairment in cancer survivors, in addition to insomnia and mood. Future randomized controlled trials with larger samples and objective measurements of cognition are needed. Support: Nyissa Walsh is a trainee in the Cancer Research Training Program of the Beatrice Hunter Cancer Research Institute (BHCRI). Dr. Sheila Garland is supported by a Scotiabank New Investigator Award from BHCRI.